2014
DOI: 10.1089/ten.tea.2013.0198
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Core–Shell Fibrous Collagen-Alginate Hydrogel Cell Delivery System for Bone Tissue Engineering

Abstract: Three-dimensional matrices that encapsulate and deliver stem cells with defect-tuned formulations are promising for bone tissue engineering. In this study, we designed a novel stem cell delivery system composed of collagen and alginate as the core and shell, respectively. Mesenchymal stem cells (MSCs) were loaded into the collagen solution and then deposited directly into a fibrous structure while simultaneously sheathing with alginate using a newly designed core-shell nozzle. Alginate encapsulation was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 26 publications
3
67
0
1
Order By: Relevance
“…Similarly, a recently designed fiber made of collagen core / alginate shell also demonstrated that rat MSCs encapsulated in the collagen core tended to form active cellular processes at the core/shell border areas to achieve better nutrients and oxygen supplies from the outer environments, which consequently became functional in forming neo-bone structure in vivo [26] (as illustrated in Fig. 13).…”
Section: Tissue Engineeringmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, a recently designed fiber made of collagen core / alginate shell also demonstrated that rat MSCs encapsulated in the collagen core tended to form active cellular processes at the core/shell border areas to achieve better nutrients and oxygen supplies from the outer environments, which consequently became functional in forming neo-bone structure in vivo [26] (as illustrated in Fig. 13).…”
Section: Tissue Engineeringmentioning
confidence: 88%
“…Alginate is thus among the most commonly used polymers for the shell as it can crosslink easily in divalent solution while maintaining the hydrogel shape [25,26]. On the other hand, many cell compatible hydrogels can be used for the core including collagen, hyaluronic acid, and fibrin [26][27][28].…”
Section: Microfibersmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Xiong et al [41] Figure 2. 3D cell printing with modified crosslinking processes, (a) aerosol crosslinking process with calcium chloride using an alginate-based bioink [36][37][38] , (b) drop-on-demand (submerged) crosslinking with a laser-assisted printing process [41] , (c) submerged printing with a core (MSC-laden collagen) /shell (2-5 wt% alginate) nozzle [44] , and (d) cell printing process with a crosslinked solution and absorbing stage using a core (3 wt% alginate-based cell-laden bioink)/shell (1.2 wt% CaCl 2 ) [46] . applied a similar method to the laser-assisted cell printing process, which contains the same limitations in printing 3D structures, and they were able to fabricate a 3D structure with a height of 9.5 mm.…”
Section: Cell Printing With Modified Crosslinking Processesmentioning
confidence: 99%
“…For applications in extrusion-based cell printing, a dual or core/shell nozzle is occasionally used as an alternative crosslinking method, as in the study described above [43][44][45][46] . The core/shell fibrous collagenalginate hydrogel was proposed by Perez et al [44] ( ).…”
Section: Cell Printing With Modified Crosslinking Processesmentioning
confidence: 99%